Peripheral intravenous cannulas for blood drawing: Nurses' views through content analysis. Issue 4 (August 2021) - Jacob, Elisabeth R.; Jacob, Alycia M.; Davies, Hugh T.; Stoneman, Laurita J.; Coventry, Linda
Abstract: Background: Peripheral intravenous cannulas are commonly used for blood sampling. Conflicting evidence on the safety and reliability of blood sampling from peripheral intravenous cannulas provides little support to guide practice of clinicians. Aim: To elicit views of nurses working in acute care of their opinions on the safety and efficacy of obtaining blood samples from peripheral intravenous cannulas. Methods: A cross-sectional electronic survey was utilised. Participants included nurses working in Australian acute care services nationally. The STROBE checklist was followed. The survey was distributed by two professional nursing bodies to their members between September and December 2017. Content analysis was used to analyse open-ended responses. Findings: Of the 338 participants who completed the survey, 269 provided comments. Themes supporting the use of peripheral intravenous cannulas for blood sampling included 'efficiency', 'patient care', 'last resort', and 'other'. Reasons for not using a peripheral intravenous cannula for sampling provided themes of 'PIVC use', 'dwell time', 'test type required', 'patency/insertion site care', 'preference', and 'other'. Discussion: The choice regarding method of blood sampling is left to the discretion of individual practitioners. Diverse rationales were provided by respondents to support their practice in sampling blood. This may be influenced by variations in hospital policies and conflicting research evidence to support or refute the practice. Conclusion: Blood sampling from peripheral intravenous cannulas or venepuncture is practiced differently between nurses based on multiple rationales. Research is needed to provide evidence for safe practice and support hospital policies.